The modular mind and psychiatry: toward clinical integration with a focus on self-disorders - Ilie, Gheorghe; Jaeggi, Adrian V. (Frontiers in Psychology, 2025)
One of the foundational tenets of evolutionary psychology, the modular view of the mind, offers promising applications for clinical psychiatry. This perspective conceptualizes the mind as a collection of specialized information-processing modules, shaped by natural selection to address adaptive challenges faced by our ancestors. In this paper, we propose several points of integration between the modularity framework and clinical psychiatric practice. First, we argue that the descriptive psychopathology of self-disorders provides evidence supporting the modular view, demonstrating how a dysfunctional minimal self may expose the mind's modular architecture to conscious awareness. Next, we will explore how the modular perspective can illuminate the nature of intrapsychic conflicts. Finally, we will discuss how evidence from neuropsychiatric syndromes supports the modular view of the mind and, in turn, how this perspective can provide a basis for classifying mental disorders.